ANALISIS PENGARUH BUDAYA ORGANISASI, LINGKUNGAN KERJA, DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA ALFAMART WILAYAH KOTA SEMARANG) - Mulyono, Arif Hei; Widodo, Untung (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This research aims to find out whether organizational culture, work environment, and compensation affect employee performance. The sample used in this research was 220 respondents from Alfamart employees in the Semarang City area. The data collection method used was a questionnaire distributed to Alfamart employees in the Semarang City area using a Google Form link distributed via the WhatsApp application. The sampling technique used is a non-probability sampling technique with a purposive sampling approach, namely the researcher chooses a purposive sample subjectively.  Data analysis in this study used Multiple Linear Regression Analysis by looking at the t statistical value, F statistic, and coefficient of determination (R Square). Based on the results of the analysis, it shows that the variables Organizational Culture and Compensation are stated to have no partial effect on employee performance, while the work environment has a positive and significant effect on Employee Performance, but not simultaneously or together, the variables Organizational Culture, Work Environment, Compensation has a positive and significant effect on employee performance, with a coefficient of determination (Adjusted R Square) obtained at a value of 0.009. This means that only 9% can be explained by the three independent variables, namely organizational culture, work environment and compensation. And the remaining 91% is explained by other variables that are not in this study.Keywords: Organizational Culture, Work Environment, Compensation, and Employee Performance